Psychological Capital Questionnaire - Short Version (PCQ-12): evidence of Validity of The Brazilian Version - Kamei,Helder (2018)
Abstract This study aimed to show evidence of validity for the Brazilian short version (12 items) of the Psychological Capital Questionnaire (PCQ-12). Three independent samples participated in the study, totaling 1771 subjects (64.3% women, 32.9% men and 2.9% undeclared), aged 18-79 years (M = 38.59, SD = 12.98). Confirmatory factor analyses showed acceptable adjustment indices for the four-factor structure (self-efficacy, hope, resilience and optimism) and for a second-order structure with a general factor of psychological capital explaining the four primary factors. Multi-group confirmatory factor analyses found configural, metric and scalar invariance of the measure for the different samples as well as for men and women. Finally, convergent validity analyses found a positive and moderate correlation of PCQ-12 with satisfaction with life and subjective happiness, as well as a negative and moderate correlation with perceived stress and depression.